1997
DOI: 10.1038/nm1097-1129
|View full text |Cite
|
Sign up to set email alerts
|

Testis-derived Sertoli cells have a trophic effect on dopamine neurons and alleviate hemiparkinsonism in rats

Abstract: Neural tissue transplantation has become an alternative treatment for Parkinson's disease (PD) and other neurodegenerative disorders. The clinical use of neural grafts as a source of dopamine for Parkinson's disease patients, although beneficial, is associated with logistical and ethical issues. Thus, alternative graft sources have been explored including polymer-encapsulated cells and nonneural cells (that is, adrenal chromaffin cells) or genetically modified cells that secrete dopamine and/or trophic factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 18 publications
0
55
0
Order By: Relevance
“…Finding the male counterpart of these stem/progenitor cells (eg, testis-derived cells) will further advance the potential for autologous transplantation. Of interest, we have shown that testis-derived Sertoli cells stand as effi cacious transplantable cells for CNS disorders [66,67], although Sertoli cells are likely not stem cells. Sex-specifi c stem cell sources may reveal an evolutionary gender difference.…”
Section: Figmentioning
confidence: 99%
“…Finding the male counterpart of these stem/progenitor cells (eg, testis-derived cells) will further advance the potential for autologous transplantation. Of interest, we have shown that testis-derived Sertoli cells stand as effi cacious transplantable cells for CNS disorders [66,67], although Sertoli cells are likely not stem cells. Sex-specifi c stem cell sources may reveal an evolutionary gender difference.…”
Section: Figmentioning
confidence: 99%
“…An additional weight-matched group of adult male Sprague-Dawley rats (nϭ10) served as positive controls (ie, nonstroke, nontransplanted, no drug treatment). Behavioral tests 12,14 were conducted at day 3 after stroke, and thereafter, animals were euthanized for histological analysis of HUCB cell survival. To reveal HUCB effects on cerebral infarction, a new set of animals (nϭ10 per group) was subjected to the same treatment.…”
Section: Animalsmentioning
confidence: 99%
“…Transplantation of cerebral Sertoli's cells relieved symptoms in rats with pharmacologically induced hemiparkinsonism [ 14]. Moreover, allograft of unpurified Sertoli's cells, in combination with islets, beneath the kidney capsule of rats with STZ-induced diabetes significantly prolonged the achieved normoglycemia, as compared to controls receiving islet transplantation alone [13].…”
Section: Discussionmentioning
confidence: 96%
“…In particular, it has been demonstrated that Sertoli's cells improve in vitro functional competence of islets [12] while in vivo; they may also prolong islet allograft survival in animal models of diabetes mellitus [13]. Finally, intracerebral transplantation of Sertoli's cells relieved symptoms in rats with pharmacologically induced hemiparkinsonism [14].…”
Section: Sodiummentioning
confidence: 99%